Adjuvant properties of chitosan derivatives administered to mice with anti-rabies vaccine - K. B. Dobroskok; E. I. Yarygina; M. S. Lipatova; M. S. Kalmykova (Ветеринария сегодня)
Searching for a preparation that would meet all the requirements for modern adjuvants remains a matter of critical importance for specific immunoprophylaxis. Much information is available now on chitosan positive effect, including its effect on the immune response. The article provides results of the preclinical tests for different affordable chitosan-based products. For the test purposes, we took the following three products manufactured by LLC Bioprogress (Shchelkovo, Russia): water-soluble chitosan (succinate) – 2% solution edible chitosan (water-soluble) – 2% solution; edible chitosan (acid-soluble) – 2% solution, as well as antirabies vaccine RABIKOV manufactured by Shchelkovo Biocombinat (Russia). Immunogenic properties of chitosan-based products were tested in 85–100-day-old female white laboratory mice weighing 21–35 g. The animals were divided into 37 groups (6 mice in each group). Chitosan-based products were administered subcutaneously or intramuscularly, either together with the anti-rabies vaccine or without it. Animals from the control groups received either saline solution or the vaccine only. There was also a group of intact animals. The experiment demonstrated that the water-soluble chitosan (succinate) administered subcutaneously, acid-soluble edible chitosan (at a concentration of 1:64 and more), and water-soluble edible chitosan (at a concentration of 1:108) administered subcutaneously and intramuscularly increase the level of post-vaccination anti-rabies antibodies. Thus, the tested chitosan-based products do not have any negative impact on the laboratory animals and have immunogenic properties.